An Optimization of Nanostructure Aluminum on Porous Silicon at Different Aluminum Thickness - Ramli, Nurhayati Muhd; Ahmad, Mohd Khairul; Adam, Mohammad Adzlan Danish; Mohamad, Fariza; Nayan, Nafarizal; Chin Fong, Soon; Ameruddin, Amira Saryati; Abu Bakar, Faridah; Shimomura, Masaru; Murakami, Kenji (International Journal of Integrated Engineering, 2018)
The growth of aluminum nanostructure was conducted on porous silicon substrate by depositing a layer of aluminum via thermal evaporation method. The deposition process of the aluminum nanostructure was under the annealing temperature at 350Â°C for 1 hour. The weight of aluminum was varied for each sample in order to obtain different thickness of aluminum deposited on the sample. The weight of aluminum used in this experiment were 12mg ,18mg ,50mg and 74mg with the corresponding aluminum thickness deposited of 112nm, 163nm, 205nm and 332nm. Characterization on the morphology of the sample are conducted by using Atomic force microscopy (AFM), Raman spectroscopy and IV measurements. Based on the result obtained, the optimum weight of aluminum was 50mg of aluminum since it is provide the higher conductivity value on the sample.